1993
DOI: 10.1016/0014-5793(93)81355-4
|View full text |Cite
|
Sign up to set email alerts
|

Post‐translational processing and Thr‐206 are required for glycosylasparaginase activity

Abstract: Lysosomal glycosylasparaginase is encoded as a 36.5 kDa polypeptide that is post‐translationally processed to subunits of 19.5 kDa (heavy) and 15 kDa (light). Recombinant glycosylasparaginase has been expressed in Spodoptera frugiperda insect cells enabling the precursor and processed forms to be isolated and their catalytic potential determined. Only the subunit conformation was functional indicating glyeosylasparaginase is encoded as an inactive zymogen. The newly created amino terminal residue of the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Thr-152 is also the key catalytic amino acid in autoproteolysis because it nucleophilically attacks the adjacent Asp-151, allowing the peptide bond between them to be broken and an active enzyme to be formed with a free ␣-amino group at the N terminus of the ␤ subunit (12,17). Previous mutagenesis studies on the human enzyme indicated that reductions of glycosylasparaginase activity in many cases are due to a slowing down of precursor autoproteolysis such that the enzyme is incompletely activated (13,14,24). This complexity in glycosylasparaginase processing creates experimental difficulties when investigating the function of specific amino acids in the mechanism of enzyme catalysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thr-152 is also the key catalytic amino acid in autoproteolysis because it nucleophilically attacks the adjacent Asp-151, allowing the peptide bond between them to be broken and an active enzyme to be formed with a free ␣-amino group at the N terminus of the ␤ subunit (12,17). Previous mutagenesis studies on the human enzyme indicated that reductions of glycosylasparaginase activity in many cases are due to a slowing down of precursor autoproteolysis such that the enzyme is incompletely activated (13,14,24). This complexity in glycosylasparaginase processing creates experimental difficulties when investigating the function of specific amino acids in the mechanism of enzyme catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its crystal structure, amino acid mutagenesis studies (13,16,17), and molecular dynamics calculations (30), glycosylasparaginase has a similar catalytic mechanism (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since glycosylasparaginase does not possess protease activity per se, the activation cannot be an autocatalytic process. It is a spontaneous intramolecular reaction with the key Based on the data presented here and in other published studies (5,6), we propose the following model of autoproteolysis of glycosylasparaginase, illustrated in Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage is essential for GA hydrolase activity and occurs at the amide bond in the consensus site between residues Asp151 and Thr152 (Ikonen et al, 1993;Fisher et al, 1993;Tarentino et al, 1995). This conserved threonine is thought to play central roles in both hydrolase activity (Kaartinen et al, 1991;Fisher et al, 1993) and autoproteolysis (Guan et al, 1996). Like other recently discovered protein autoprocessing pathways, GA self-catalyzes peptide-bond rearrangement through an N3O or N3S acyl shift (Perler, 1998a;Paulus, 1998).…”
Section: Introductionmentioning
confidence: 99%